Penatalaksanaan Target Temperatur Manajemen Pada Pasien Henti Jantung Dengan Irama Non-Shockable: Literature Review - Nirmana, Kurniasani; Hidayah, Nurul; Masithoh, Robiul Fitri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: This literature review study aims to determine the management of target temperature management in cardiac arrest patients with non-shockable rhythms.Methods: The research design used is a literature review. Article search engines use Science Direct, PubMed, and Google Scholar. The keywords used include